Relevance of human fat distribution on lipid and lipoprotein metabolism and cardiovascular disease risk - Piché, M; Vasan, S; Hodson, L; Karpe, F (Lippincott, Williams and Wilkins, 2018)
Purpose of review Upper body abdominal and lower body gluteofemoral fat depot masses display opposing associations with plasma lipid and lipoprotein and cardiovascular disease (CVD) risk profiles. We review developments on adipose tissue (AT) fatty acid (FA) metabolism in the context of body fat distribution and how that might be related to adverse lipid and lipoprotein profiles and CVD risk. Recent findings Recent data have confirmed the paradoxical relationship of upper abdominal and lower body gluteofemoral adiposity and CVD risk. Mechanistically this is likely to reflect the different ways fat depots handle lipid storage and release, which impacts directly and indirectly on lipid and lipoprotein metabolism. The upper body enhances immediate fat storage pathway with rapid uptake of dietary-derived FAs, whereas the lower body fat depot has a reduced lipid turnover accommodating a slower fat redistribution. Body fat distribution and the fat depots’ ability to undergo appropriate expansion when fat storage is required, rather than overall body fatness, appear as the important determinant of metabolic health. Summary A focus on fat distribution in overweight people, preferably using precise imaging methods, rather than quantifying total body fatness, is likely to provide the medical community with better tools to stratify and treat patients with obesity-related complications.